Driving to the "Net": Blogs, Frames, and Politics in the New York Islanders' Stadium Saga. (February 2015) - Norman, Mark; Ventresca, Matt; Szto, Courtney; Darnell, Simon C.
On October 24, 2012, the New York Islanders of the National Hockey League announced a plan to move from their current stadium in Nassau County to the recently opened Barclays Center in the borough of Brooklyn, marking the end of a decades-long political saga about whether and where to build a new home arena for the club. During this time, the Islanders franchise strove to mobilize support for the ostensible benefits of the stadium development and the importance of the team for the local community and economy. In this article, we offer an analysis of the ways in which such processes were interpreted, supported, and/or resisted by some of its highly invested fans through the act of blog writing. Based on content analysis and interviews, the results suggest that bloggers saw little choice but to support plans that kept the team as close to Nassau County as possible. We use this data to discuss the hegemony of neoliberalism as an organizing principle of professional sport, the agency of fans that negotiate such politics when supporting their club, and the Internet as a platform for communication and potential collective action in sport.